TAX AVOIDANCE, FINANCIAL PERFORMANCE, COPORATE GOVERNACE, AND FIRM VALUE - Deyanira Safitri; Erina Sudaryati (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The purpose of this study was to examine the effect of tax avoidance, financial performance, corporate governance on firm value. Financial performance proxies are return on assets, return on equity, size and leverage. Meanwhile, the proxy for corporate governance is the audit committee. This study uses a sample of all companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 except for financial companies. The final sample in this study was 1,158 companies. This study uses multiple linear regression data analysis techniques. Firm value is measured using Tobin's Q. Based on the results of hypothesis testing, the results show that tax avoidance has a negative effect on firm value. Furthermore, for return on assets, return on equity and leverage have a positive effect on firm value. However, the size and audit committee variables have no effect on firm value